2020
DOI: 10.3892/etm.2020.9416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of atovaquone on EpCAM<sup>+</sup>CD44<sup>+</sup> HCT‑116 human colon cancer stem cells under hypoxia

Abstract: Tumor hypoxia contributes to the development of resistance to chemotherapeutic drugs in several human cancer cell lines. Atovaquone, an anti-malaria drug approved by the US Food and Drug Administration, has recently demonstrated anti-cancer effects in vitro and in vivo in several cancer models. To assess the potential of atovaquone as an anti-cancer agent under hypoxia in colorectal carcinoma, EpCAM + CD44 + colon cancer stem cells were isolated from HCT-116 human colon cancer cells through magnetic-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, Xie et al reported that overexpressing microRNA-34a overcame ABCG2-mediated drug resistance to 5-FU in SP cells from colon cancer via suppressing DLL1 [29]. Another study showed the efficacy of atovaquone on EpCAM + CD44 + HCT-116 human colon cancer stem cells under hypoxia [40]. In this study, the EpCAM + CD44 + CSC also expressed increased mRNA levels of pluripotency genes such as Nanog, Sox2, Oct4 (aka.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, Xie et al reported that overexpressing microRNA-34a overcame ABCG2-mediated drug resistance to 5-FU in SP cells from colon cancer via suppressing DLL1 [29]. Another study showed the efficacy of atovaquone on EpCAM + CD44 + HCT-116 human colon cancer stem cells under hypoxia [40]. In this study, the EpCAM + CD44 + CSC also expressed increased mRNA levels of pluripotency genes such as Nanog, Sox2, Oct4 (aka.…”
Section: Discussionmentioning
confidence: 56%
“…Fu et al (2020) stated that atovaquone, which usually treats malaria infection, can be used against positive CD44 and EpCAM cancer cells. Atovaquone stopped the proliferation by blocking S-phase under hypoxia, which causes apoptosis to CSCs, but the authors stated that the study has some limitations during the trial process, which may affect the apoptotic rate; this calls for further research to be conducted [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, atovaquone was reported as a promising anti-cancer agent that is effective against cancer cells and cancer stem cells. The application of atovaquone increase radiosensitivity by alleviating tumour hypoxia, thus suggesting its high potential in combination with other anti-cancer drugs [ 93 , 94 ]. In ATC and FTC cell cultures, atovaquone decreases growth, migration, and survival by inhibiting mitochondrial complex III activity and subsequently reducing ATP production.…”
Section: Thyroid Cancer Treatmentmentioning
confidence: 99%